Scaling up coral spawn collection: Impacts of method and timing on Acropora valida larval quality - Christina Langley; Christopher Doropoulos; Dexter dela Cruz; Peter L. Harrison (PLoS ONE, 2025)
Scaling up coral reef restoration to ecologically relevant scales presents a significant challenge during propagule collection. Mass coral spawning events are a vast source of propagules for reef restoration, but these events are typically limited to a few nights annually. Various methods of spawn collection following spawning events are available, ranging from traditional small-scale collection to industrial large-scale collection. However, comparisons between methods and potential effects on larval integrity are poorly understood. In this laboratory-based study, different methods of spawn collection – buckets, nets, and diaphragm pumping – were tested at various time points following spawning to explore potential impacts on embryo integrity, larval size, rate of deformities, and larval settlement. Results indicated that the collection method and, especially, the timing of collection, were critical. While bucket collection had minimal impact on embryo integrity, net and pump techniques caused high embryo fragmentation (>45%) at 5–11 hours post-fertilisation when embryos were >8 cells. This significantly reduced the average size of developing larvae in net and pump collections 3–11 hours post-fertilisation. When collections took place within the first hour of fertilisation before embryo cleavage, using any collection method resulted in minimal fragmentation (<4%). In general, net samples had larger larvae than pumped samples. However, larger larvae appeared to be more prone to deformities, and deformed larvae exhibited reduced settlement success (4% deformed vs 25% intact). These results highlight how large-scale spawn collections can be conducted without compromising larval quality when timed carefully, offering practical guidance for scaling coral reef restoration efforts.